In Search of the Poem: Derrida and the Question of the Poematic - Gogoi, Arnav (Journal of Advanced Research in English & Education, 2023)
What does it mean to ask, “What is Poetry?” One could consider the slight possibility that the nature of the question in this instance assumes a certain positioning of an answer that already comes before the question. We are already in the familiar territory of “yes,” where the question directs itself in its questioning. The subject “Poetry” precedes itself in such an instance. It returns from the site of the familiar, brings with it a tendency to face the question and say “It is” However, the problem with such an “It is” is the perpetual repetition of the possibility of an answer where poetry finds a ground for its being. If such is the case, then why bother asking the question “What is” if the answer to it already exists within the domain of knowledge? Is it possible that a rift exists between this questioning and answering, which we always try to bridge through a hyphen? A hyphenation that holds the question and the answer together in a state of repeatability? In this light, this paper seeks to look at Derrida’s essay “Che cos’ è la poesia?” and underline the problem of the poetic, which takes place at the site of this hyphenation, thereby de-familiarising the familiar terrain of the question of poetry. It will attempt a possible theorization of this domain of the poem, which unsettles existing structures of knowledge. The argument would be to see what happens in the bridging, where poetry survives as a shibboleth.